Exploring Foreign Language Anxiety Across Language Skills : Evidence from Pakistani ESL Undergraduates - Farhad, Ullah; Rokiah, Paee; Joseph, Ramanair (RSIS International, 2025)
Foreign language anxiety is one of the most persistent challenges in second language learning, often reducing learners’ confidence and participation. This study investigated the levels of anxiety across five domains : speaking, classroom, writing, listening, and reading among ESL undergraduates in Pakistan. A total of 381 students from three universities completed a 27-item questionnaire designed to capture domain-specific anxieties. The results showed that learners experienced moderate anxiety overall (M = 3.12, SD = 0.88). Among the domains, speaking (M = 3.34) and classroom anxiety (M = 3.26) were the most pronounced, highlighting oral and evaluative settings as the strongest sources of stress. In contrast, reading (M = 2.83) was the least anxiety-inducing, while writing and listening reflected moderate levels. These findings indicate that learners are most vulnerable when required to perform spontaneously or respond in classroom contexts, whereas individual and receptive tasks generate relatively less anxiety. The study underscores the importance of supportive, student-centered classrooms that reduce evaluation pressure and build confidence in oral performance. Collaborative activities, low-stakes speaking tasks, and constructive feedback can help alleviate anxiety, while scaffolding supports receptive and written tasks. Limitations include reliance on self-reports and a sample from three universities. Future research should adopt mixed-methods and longitudinal designs to capture how anxiety evolves and evaluate interventions over time.